Reporting on Africa: From Apartheid to Pan-Africanism, 1949-1995. (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2013)
Colin Legum (1919-2003) was a South African journalist and writer on African politics. Born in a rural farming town of Kestell, his worldview was shaped by the degrading poverty and racial injustice he witnessed in his hometown. This experience fed his passion for political reporting and he got his first job in journalism at the age of 15 for a Johannesburg newspaper called the Sunday Express. Legum could not tolerate the Apartheid government that seized power in South Africa in 1948 and left for Britain the following year. Working for the Observer, he became well known for his anti-Apartheid writing and helped popularise African history with the British public. This collection contains a range of his writings and reports on 20th century African politics. This includes material on Pan-Africanism, including on the Organisation of African Unity, articles documenting and attacking the Apartheid regime in South Africa, as well as exploration of African politics against the back drop of decolonisation and the Cold War. Legum only returned to South Africa in 1991 when he was politically able to, living there until his death in 2003.
Date range: 1949-1995.
Keywords: Legum, Colin; Apartheid -- South Africa -- History -- 20th century; Africa -- History -- 20th century